2009
DOI: 10.1093/treephys/tpp047
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defences and oxidative damage in salt-treated olive plants under contrasting sunlight irradiance

Abstract: The interactive effects of root-zone salinity and sunlight on leaf biochemistry, with special emphasis on antioxidant defences, were analysed in Olea europaea L. cv. Allora, during the summer period. Plants were grown outside under 15% (shade plants) or 100% sunlight (sun plants) and supplied with 0 or 125 mM NaCl. The following measurements were performed: (1) the contribution of ions and soluble carbohydrates to osmotic potentials; (2) the photosystem II (PSII) photochemistry and the photosynthetic pigment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 56 publications
1
30
0
2
Order By: Relevance
“…Phenolic compounds and flavonoids tend to accumulate in the epidermis and mesophyll of tropical trees under intense irradiance (Melgar et al, 2009), as observed in plants of C. echinata in full sun. However, the presence of phenols was also observed in the epidermis of leaves of C. echinata under shade.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Phenolic compounds and flavonoids tend to accumulate in the epidermis and mesophyll of tropical trees under intense irradiance (Melgar et al, 2009), as observed in plants of C. echinata in full sun. However, the presence of phenols was also observed in the epidermis of leaves of C. echinata under shade.…”
Section: Discussionmentioning
confidence: 83%
“…However, the presence of phenols was also observed in the epidermis of leaves of C. echinata under shade. The accumulation of phenols, especially quercetin glycosides luteolin, indicates an efficient antioxidative defense system (Guidi et al, 2008) acting in the scavengers of several reactive oxygen species (ROS) and singlet O 2 in the chloroplasts of plants under intense irradiance (Melgar et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations